Students’s performance and utilization of Universitas Indonesia Library during the pandemic - Yulistiana Prasetya; Rahmi Rahmi (Universitas Padjadjaran, 2022)
Academic libraries are the university's heart. However, studies on the relationship between library use and student performance are sparse. This study contributes to research on the relationship between library use and student performance. This study aimed to examine the relationship between library use of the Universitas Indonesia Library online (accessing through https://lib.ui.ac.id) and on-site (visiting the library) and library science undergraduate students' performance (Grade Point Average) on library science at Universitas Indonesia during pre-pandemic compared to during the pandemic. This study used a quantitative approach through survey research methods. Research respondents is 54 student that participating before and during the pandemic through data analysis chi-square and correlation analysis. The results showed a weak correlation between online and on-site library use and student performance. There was a significant relationship between online and on-site library use and demographic characteristics (gender, age, and year of enrolment).High-level students used the library more pre-pandemic than lower-level students. During the pandemic, students used electronic collections facilities outside the library website. The use of the library supports the improvement of student performance. This study contributed to introducing a data collection approach for assessing and making decisions about the library users needs, resources, and services. The study concludes that academic libraries are continuously improving their performance in contributing to achieving institutional goals and student success before and during the pandemic.